Effects of a non native species of Poaceae on aquatic macrophyte community composition: A comparison with a native species - De Amorim, Sara Regina; Umetsu, Cristiane Akemi [UNESP]; Toledo, Douglas; Camargo, Antonio Fernando Monteiro [UNESP] (My University, 2015)
Invader-dominated systems of exotic species frequently damage native communities, mainly because there is a shift in the competition-facilitation balance, and competition intensifies in communities structured by facilitation. We tested whether areas dominated by the exotic species African signalgrass [Urochloa arrecta (Hack, ex T. Dur. & Schinz) O. Morrone & F. Zuloaga] can affect the assemblage structure of aquatic plants in tropical freshwater ecosystems, compared with the native species, anchored water-hyacinth [Eichhornia azurea (Sw.) Kunth]. We predicted that the dominance of African signalgrass (expressed as an increase in biomass) would reduce species richness, diversity, and functional diversity of the macrophyte assemblages, when compared with anchored waterhyacinth. Species cover and the occurrence of associated species were assessed in quadrats (1 m), located in sites dominated by exotic species (African signalgrass), native species (anchored waterhyacinth), and without dominance. The effects of dominance on species richness and diversity of aquatic macrophytes were assessed through generalized linear model and composition with detrended correspondence analysis. African signalgrass negatively affected species richness and Shannon diversity, whereas anchored waterhyacinth showed no effects on species richness and Shannon diversity. However, native species positively affected functional diversity. Our study showed that invasive species reduced the presence of rooted-submerged species, whereas native species facilitated the occurrence of rooted-submerged and free-submerged species. Thus, African signal-grass was able to change the composition of the macrophyte assemblage and can represent a threat to native communities of tropical freshwater ecosystems.
Keywords: Dominance; Eichhornia azurea; Exotic species; Generalized linear models; Tropical freshwater ecosystems; Urochloa arrecta